Usefulness of heart rate variability indices in assessing the risk of an unsuccessful return to work after sick leave in depressed patients. Issue 3 (5th July 2020) - Shinba, Toshikazu; Murotsu, Keizo; Usui, Yosuke; Andow, Yoshinori; Terada, Hiroshi; Takahashi, Mami; Takii, Rie; Urita, Michiko; Sakuragawa, Satoshi; Mochizuki, Miwa; Kariya, Nobutoshi; Matsuda, Saori; et al.
Abstract: Aim: The present study aimed to examine whether heart rate variability (HRV) indices in depressed patients measured at return to work after sick leave are related to the outcome of reinstatement. Methods: This study included 30 workers who took a leave of absence due to major depressive disorder. HRV was measured twice, once when participants left work and another when they returned to work. One month after returning to work, 19 participants continued their original work (successful return group), while 11 failed to perform their original work (unsuccessful return group). HRV indices including high‐ and low‐frequency components (HF and LF) were calculated in three conditions within a session lasting for about 5 minutes, initial rest (Rest), mental task (Task), and rest after task (After), and were compared between the two participant groups. Psychological states were evaluated using Self‐rating Depression Scale and State‐Trait Anxiety Inventory. Results: No significant differences were observed in the HRV indices on leaving work between groups. On returning to work, the "unsuccessful return group" exhibited lower HF Rest score, higher HF Task/Rest ratio, and higher LF/HF Rest score than the "successful return group." Psychological scores improved in both groups. Conclusion: These results indicate that autonomic dysregulations revealed by HRV measurement at return to work after a leave of absence in MDD patients were related to the outcome of reinstatement and can serve as useful information for the assessment of the risk of unsuccessful return. Abstract : Autonomic dysregulations revealed by heart rate variability measurement at return to work after sick leave in depressed patients were related to the outcome of reinstatement and can serve as useful information for the assessment of the risk of unsuccessful return.